(untitled) (Annual of the Faculty of Philosophy in Skopje, 2023)
Parenting a child with a disability presents unique challenges and requires additional care and attention. Parents play a crucial role in promoting their child’s development, fostering their independence, and nurturing their overall well-being. This research study aims to investigate the adequacy of resources and support available to families of children with disabilities, as well as the perception of parents regarding these aspects. A specially designed questionnaire consisting of 21 questions was used as the research instrument, which was distributed to families through a Google form. The research sample was convenience-based and comprised 250 parents of children with disabilities. The findings of the study reveal widespread dissatisfaction among parents in relation to institutional support. The results indicate that a significant majority of parents (80%) do not receive adequate institutional support, while only 1% reported receiving it. Furthermore, not a single parent reported being satisfied with the coordination among medical, educational, and social institutions, with 56% expressing dissatisfaction and 44% indicating partial satisfaction. This study highlights the need for improved coordination among various institutions, increased parent education, and the provision of comprehensive support services to ensure a better quality of life for families of children with disabilities.